Visual meetings : how graphics, sticky notes & idea mapping can transform group productivity - Sibbet, David (Hoboken, N.J. : John Wiley & Sons, 2010)
'Use eye-popping visual tools to energize your people! Just as social networking has reclaimed the Internet for human interactivity and co-creation, the visual meetings movement is reclaiming creativity, productivity, and playful exchange for serious work in groups. Visual Meetings explains how anyone can implement powerful visual tools, and how these tools are being used in Silicon Valley and elsewhere to facilitate both face-to-face and virtual group work. This dynamic and richly illustrated resource gives meeting leaders, presenters, and consultants a slew of exciting tricks and tools, including graphic recording, visual planning, story boarding, graphic templates, idea mapping, etc.; creative ways to energize team building, sales presentations, staff meetings, strategy sessions, brainstorming, and more; getting beyond paper and whiteboards to engage new media platforms; understanding emerging visual language for leading groups. Unlocking formerly untapped creative resources for business success, Visual Meetings will help you and your team communicate ideas more effectively and engagingly'--
Includes bibliographical references and index.
Keywords: Teams in the workplace; Business meetings; Visual communication